Dielectric Strength And Electrical Surface Tracking Characteristics Of Sir Epdm Containing Alumina And Titanium Nano-Fillers For High Voltage Insulators - Muhamad Raslani, Muhamad Fairus Adzha (2016)
Nowadays, the combination of polymer materials such as SiR and EPDM as a rubber-rubber composite has become one of the main research in developing new polymer insulator with superior characteristics. Recently, the researchers found that SiR/EPDM with formulation of 50:50 weight percentages ratio blends had produced the optimal electrical and mechanical properties of the polymer composites. However, until now the study of these balanced blends with inclusion nano-fillers on the electrical, mechanical and surface tracking characteristics are still few and has not been fully explored yet. Hence, in this research, the SiR/EPDM blends were prepared with two types nano-fillers such as Al2O3 and TiO2. The loading concentration of nano-fillers for each specimen is 1 Vol%, 2 Vol%, 3 Vol%, 4 Vol%, and 5 Vol%. The effects of Al2O3 and TiO2 nano-fillers with different loading concentrations on the dielectric properties, tensile strength, and surface tracking characteristics were investigated. The experiment results revealed that the inclusion 1 Vol% loading concentration of Al2O3 and TiO2 nano-fillers in SiR/EPDM have increased the dielectric and tensile strength as compared to UnF SiR/EPDM. On the other hand, both nano-composite (all loading concentrations) showed that the value of the dielectric constant increases when the loading concentration of nano-filler was increased from 1 Vol% to 5 Vol%. While the values of dielectric loss reduced as the frequency of testing increased. The results also demonstrated that the addition of nano-fillers in SiR/EPDM composite was significantly improved the electrical surface tracking resistance performance which slowing the aging process or minimizes damage to the surface. The experimental results showed that the SiR/EPDM filled with 1 Vol% Al2O3 nano-filler has better tracking time performance comparable to SiR/EPDM filled with 2 Vol% TiO2 nano-filler. Finally, the tracking time and thermal conductivity characteristics of both nano-composites are higher than UnF SiR/EPDM.